IMPLEMENTASI DAN DAMPAK PROGRAM CORPORATE SOCIAL RESPONSIBILITY BRI PESAT TERHADAP HARGA KIOS LOS DAN TOKO DALAM UPAYA PEMBERDAYAAN PASAR SEHAT CILEUNYI: (Studi Kasus pada Pedagang Pasar Sehat Cileunyi) - Dwiyanisa, Ashila (Majalah Bisnis & IPTEK, 2021)
This research was conducted to find out how the implementation of CSR program of PT Bank Rakyat Indonesia Tbk, which is BRI program Fast (Peduli Pasar Rakyat) in Cileunyi Healthy Market, Bandung regency. As is known, factually, traditional market conditions in Indonesia are generally very poor, besides the lack of public facilities and other infrastructure such as inadequate roads as well as unprofessional market management, resulting in irregular (slum and dirty) market conditions, BRI tries to help the community Traders change the conditions of traditional markets to be better, cleaner, comfortable and interesting to visit. BRR’s Community Development CSR Program is one of the BRI Peduli Sarana Umum programs aimed at empowering traditional market communities by making traditional markets an attractive, clean, comfortable and secure trading center, the developers should better understand the objectives of BRI’s CSR program so that activities CSR is really to help the surrounding community. This research uses qualitative method with case study research. The author conducted in-depth interviews, participatory observation and documentation as a data collection technique. The results of this study are expected to be useful information for further research. Keywords: corporate social responsibility, healthy market cileunyi.